Sarcopenic obesity in rheumatoid arthritis: prevalence and impact on physical functioning. (24th September 2021) - Baker, Joshua F; Giles, Jon T; Weber, David; George, Michael D; Leonard, Mary B; Zemel, Babette S; Long, Jin; Katz, Patricia
Abstract: Objective: We determined the prevalence of sarcopenic obesity in patients with RA using multiple methods and assessed associations with physical functioning. Methods: This study evaluated data from three RA cohorts. Whole-body dual-energy absorptiometry (DXA) measures of appendicular lean mass index (ALMI, kg/m 2 ) and fat mass index (FMI) were converted to age, sex and race-specific Z-Scores and categorized using a recently validated method and compared it to a widely-used existing method. The prevalence of body composition abnormalities in RA was compared with two reference populations. In the RA cohorts, associations between body composition and change in the HAQ and the Short Physical Performance Battery (SPPB) in follow-up were assessed using linear and logistic regression, adjusting for age, sex, race and study. Results: The prevalence of low lean mass and sarcopenic obesity was higher in patients with RA (14.2; 12.6%, respectively) compared with the reference population cohorts (7–10%; 4–4.5%, respectively, all P <0.05). There was only moderate agreement among methods of sarcopenic obesity categorization (Kappa 0.45). The recently validated method categorized fewer subjects as obese, and many of these were categorized as low lean mass only. Low lean mass, obesity and sarcopenic obesity were each associated with higher HAQ and lower SPPB at baseline and numerically greater worsening. Conclusion: RA patients had higher rates of low lean mass and sarcopenic obesity than the general population. The recently validated methods characterized body composition changes differently from traditional methods and were more strongly associated with physical function.